The Developmental Phases of Zebrafish Myogenesis - Keenan, Samuel R. (J Dev Biol, 2019)
The development and growth of vertebrate axial muscle have been studied for decades at both the descriptive and molecular level. The zebrafish has provided an attractive model system for investigating both muscle patterning and growth due to its simple axial musculature with spatially separated fibre types, which contrasts to complex muscle groups often deployed in amniotes. In recent years, new findings have reshaped previous concepts that define how final teleost muscle form is established and maintained. Here, we summarise recent findings in zebrafish embryonic myogenesis with a focus on fibre type specification, followed by an examination of the molecular mechanisms that control muscle growth with emphasis on the role of the dermomyotome-like external cell layer. We also consider these data sets in a comparative context to gain insight into the evolution of axial myogenic patterning systems within the vertebrate lineage.